Average Error: 0.0 → 0.0
Time: 13.7s
Precision: 64
\[e^{-\left(A + B\right)}\]
\[e^{-\left(A + B\right)}\]
e^{-\left(A + B\right)}
e^{-\left(A + B\right)}
double f(double A, double B) {
        double r26344654 = A;
        double r26344655 = B;
        double r26344656 = r26344654 + r26344655;
        double r26344657 = -r26344656;
        double r26344658 = exp(r26344657);
        return r26344658;
}

double f(double A, double B) {
        double r26344659 = A;
        double r26344660 = B;
        double r26344661 = r26344659 + r26344660;
        double r26344662 = -r26344661;
        double r26344663 = exp(r26344662);
        return r26344663;
}

Error

Bits error versus A

Bits error versus B

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[e^{-\left(A + B\right)}\]
  2. Final simplification0.0

    \[\leadsto e^{-\left(A + B\right)}\]

Reproduce

herbie shell --seed 1 
(FPCore (A B)
  :name "exp(-(A + B))"
  (exp (- (+ A B))))